Trade-offs involved in sustainable consumption practices: A study on consumer perception - Lima, Cindy Loureen Bernardo; Sobreira, Érica Maria Caliópe; Pinho, Ana Paula Moreno; Leocádio , Áurio Lúcio (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
This article investigates how consumers perceive the trade-offs involved in sustainable consumption. It consists of an exploratory field study, with a qualitative approach, in which 9 consumers who declared themselves adept at sustainable consumption were interviewed. Most of the interviewees were aware that there are trade-offs involved in this consumption. Nevertheless, it was observed that they tend to simplify the concepts addressed, emphasizing the environmental aspect, in particular, the disposal of waste. This trend is reflected in consumption practices, which are highly focused on reuse to the detriment of other aspects of sustainability such as saving resources and non-consumption.